2016
DOI: 10.1073/pnas.1609376113
|View full text |Cite
|
Sign up to set email alerts
|

Density of immunogenic antigens does not explain the presence or absence of the T-cell–inflamed tumor microenvironment in melanoma

Abstract: Melanoma metastases can be categorized by gene expression for the presence of a T-cell–inflamed tumor microenvironment, which correlates with clinical efficacy of immunotherapies. T cells frequently recognize mutational antigens corresponding to nonsynonymous somatic mutations (NSSMs), and in some cases shared differentiation or cancer–testis antigens. Therapies are being pursued to trigger immune infiltration into non–T-cell–inflamed tumors in the hope of rendering them immunotherapy responsive. However, whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
284
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 358 publications
(313 citation statements)
references
References 40 publications
28
284
1
Order By: Relevance
“…It has been hypothesized that a higher mutational burden will correspond to a greater potential for neoantigen formation and a higher immune infiltrate [119]. The tumor types with high average mutation load such as melanoma and non-small cell lung carcinoma, as well as the most highly mutated individual tumors within these types, appear to respond better to immunotherapy [120,121], however the mutational load does not necessarily correlate with the expression of immune-related genes in the tumor or the effector T cell infiltrate [122124]. Specific mutational signatures such as homologous recombination pathway defects [125], POLE mutations, or microsatellite instability may prove to be important.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that a higher mutational burden will correspond to a greater potential for neoantigen formation and a higher immune infiltrate [119]. The tumor types with high average mutation load such as melanoma and non-small cell lung carcinoma, as well as the most highly mutated individual tumors within these types, appear to respond better to immunotherapy [120,121], however the mutational load does not necessarily correlate with the expression of immune-related genes in the tumor or the effector T cell infiltrate [122124]. Specific mutational signatures such as homologous recombination pathway defects [125], POLE mutations, or microsatellite instability may prove to be important.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis to explain cold tumors is that a network of immunosuppression develops in the tumor microenvironment as a reaction to a nascent anti-tumor T cell response and actively excludes further T cell infiltration. A recent study of TCGA data indicates that the lack of spontaneous immune infiltration in non-inflamed human melanoma tumors is unlikely due to lack of antigens per se (58). In patients with pancreas cancer, we have reported that the cytolytic index, defined by expression of granzyme A and perforin 1, is inversely proportional to the number of predicted neo-epitopes (59).…”
Section: What Are We Missing?mentioning
confidence: 99%
“…Broadly speaking, resistance mechanisms can be categorized as tumor-intrinsic, environmental, or genetic. Tumor-intrinsic molecular alterations that that may lead to resistance have been identified in human samples, such as β-catenin, FGFR3, PTEN, and JAK 1/2 [55, 5759]. Exploration into the mechanisms at play and/or their use as predictive biomarkers is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing research is aimed at understanding the mechanisms behind development of the non-T cell-inflamed, or immune resistant, phenotype. Additionally, mutational burden has been linked with improved response to immune checkpoint blockade and this characteristic appears to be independent of the T cell inflamed phenotype [55]. Yet neoantigen burden is not consistent as a predictive biomarker on its own, since there are observed responses in some patients with relatively low tumor mutational burden and vice versa.…”
Section: Therapeutic Successes and Challenges Of Immune Checkpoint Blmentioning
confidence: 99%